LEARNING FUNCTIONAL GRAMMAR IN ESP CLASS - Dian Arsitades Wiranegara (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
Learning functional grammar for ESP class is aimed to improve studentsof non-English language department to understand how English workseffectively, appropriately, and accurately. Teaching ESP cannot beseparated by the use or the implementation of functional grammar as it isclear that teaching English as a foreign language in ESP class is alsoconcerned with the language as an instrument of social interaction ratherthan as a system which is viewed in isolation. Teaching functionalgrammar for ESP students, in this matter, students of non-Englishlanguage department, can result such a hard working effort for teachers inorder to help them understand the-so-called functional grammar. As amatter of fact, ESP can combine subject matter of the related field ofstudy and English language teaching. Therefore, learning functionalgrammar has actually been conducted in ESP class since the students arealso involved with the use of their background knowledge of the field ofstudy.